A novel method for multipath routing using cross layer approach in vehicular adhoc networks. (22nd January 2017) - Bhagyavathi, M.; Saritha, V.; Venkata Krishna, P.
Summary: Vehicular Adhoc Network (VANET) is playing a vital role in recent research. Designing an effective routing protocol for VANET is a challenging task as the VANET nodes move very fast. The design of the routing protocol normally is particular to the specific topology. This paper proposes CLMR, a multipath routing protocol based on cross layer design and also using Redundant Array Inexpensive Disks (RAID). Cross layer is designed among application, network, Media Access Control, and physical layers. It is employed to reduce the end to end delay in network, and RAID is used to minimize the number of re‐transmissions. Three variations of RAID1 are implemented—Distributed Parity along Single path, Double Distributed Parity, and Distributed Parity among Multiple paths. Multipath routing protocol based on cross layer‐Distributed Parity along Single path recovers 1 packet loss per parity packet along the corresponding path, CLMR‐Double Distributed Parity recovers 2 packets per parity packet along the corresponding path, and CLMR‐Distributed Parity among Multiple paths recovers the packets of the failed path. The evaluation is carried out to test the Quality of Service parameters‐end to end delay, throughput, packet delivery ratio, and number of retransmissions. The results projected show that the CLMR performs better when compared with the legacy protocol Adhoc On‐demand Multipath Distance Vector Routing. Abstract : This paper proposes CLMR, a multipath routing protocol based on cross layer design and also using Redundant Array Inexpensive Disks (RAID). RAID is used to minimize the number of re‐transmissions. Three variations of RAID1 are implemented–Distributed Parity along Single path, Double Distributed Parity, and Distributed Parity among Multiple paths.